Paciente femenino con 20 semanas de gestación de 26 años de edad con antecedentes de diabetes mellitus tipo 2. - Muñoz Terán, Frank Patricio (2021)
The present case study refers to a 26-year-old female patient in gestation period with a history of type II diabetes mellitus. The patient underwent a personalized comprehensive nutritional dietary evaluation using anthropometric, biochemical, clinical and dietary indicators. Within the anthropometric parameter, data on current weight of 68.5kg, preconception weight of 64kg and height of 160cm were considered, using them as a reference to obtain weight gain values. The patient underwent two evaluation visits; the first one at 20 weeks of gestation and a weight gain of 3.1kg, the second one at 25 weeks of gestation and a weight gain of 4.6 kg considered adequate for her gestational age. In the biochemical parameter, fasting glucose values of 98 mg/dl, glucose of 140 mg/dl, glycosylated hemoglobin of 6.5% were observed, being expected results due to her history of diabetes mellitus type II. Within the clinical evaluation aspect, no alteration was observed. As for the dietary indicator, the patient was prescribed a food plan according to her nutritional and physiological needs. A diet of 2000 kcal per day was designed, hyperproteic, normoglycemic and hypoglycemic, high in fiber and divided into five meals per day. At the end of the study, the patient was monitored and followed up in order to corroborate positive progress in all the indicators evaluated.